Daya Hambat Bakteri Staphylococus Aureus Pada Ekstrak Metanol Daun Jambu Biji Merah (Psidium Guajava L. Var. Pomifera) - Muhammad Irfan Zidni; Muhammad Walid (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
Staphylococcus aureus infection is one of the causes of increasing number of diseases and deaths. It is estimated that currently around 2-3% of the general population has MRSA in their bodies. People with MRSA on their bodies are estimated to have a 64% higher chance of dying. The purpose of this study was to determine the antibacterial activity of red guava leaves against Staphylocoocus aureus bacteria and to determine the amount of inhibition of methanol extract from red guava leaves against the activity of Staphylocoocus aureus bacteria. This type of research is experimental research The object of this study is the inhibitory power of Staphylococcus aureus bacteria in methanol extract of red guava leaves. The sample used in this study was methanol extract of red guava leaves. This research was conducted using maceration extraction method with the solvent used is methanol. The measurement results showed that red guava leaf methanol extract at concentrations of 25%, 50%, 75% and 100% had an inhibitory zone on the antibacterial activity of Staphylococus aureus. The greatest bland result at a concentration of 50% of 0.49 mm. The lowest inhibitory power is at a concentration of 75% of 0.26 mm.